High-intensity interval training prescription for combat-sport athletes - Franchini, E. (International Journal of Sports Physiology and Performance, 2020)
Context: Combat sports are composed of high-intensity actions (eg, attacks, defensive actions, and counterattacks in both grappling and striking situations depending on the specific sport) interspersed with low-intensity actions (eg, displacement without contact, stepping) or pauses (eg, referee stoppages), characterizing an intermittent activity. Therefore, high-intensity interval training (HIIT) is at the essence of combat-sport-specific training and is used as complementary training, as well. HIIT prescription can be improved by using intensity parameters derived from combat-sport-specific tests. Specifically, the assessment of physiological indexes (intensity associated with the maximal blood lactate steady state, maximal oxygen consumption, and maximal sprint) or of time-motion variables (high-intensity actions, low-intensity actions, and effort:pause ratio) is a key element for a better HIIT prescription because these parameters provide an individualization of the training loads imposed on these athletes. Purpose: To present a proposal for HIIT prescription for combat-sport athletes, exemplifying with different HIIT protocols (HIIT short intervals, HIIT long intervals, repeated-sprint training, and sprint interval training) using combat-sport-specific actions and the parameters for the individualization of these protocols. Conclusions: The use of combat-sport-specific tests is likely to improve HIIT prescription, allowing coaches and strength and conditioning professionals to elaborate HIIT short intervals, HIIT long intervals, repeated-sprint training, and sprint interval training protocols using combat-sport actions, providing more specificity and individualization for the training sessions.